Utilização de xilanase comercial em sequências de branqueamento totalmente livre de cloro (TCF) de polpa Kraft de coníferas - Araújo, José Hilton Bernardino de (1997)
Several experiments have been performed at Technical Research Laboratory at Klabin Fabricadora de Papel e Celulose S.A., Divisão Paraná, to verify the performance of commercial xylanases on Totally Chlorine Free bleaching sequences of unbleached softwood kraft pulps. Combinations of oxygen "O", Pulpzyme HC (Novo Nordisk) xylanase treatment "XP", Cartazyme NS-10 (Sandoz/Clariant) xylanase treatment 'XC", acid treatment 'A", quelation "Q", and oxidative peroxide extraction "EOP" have been tested in a variety of sequences Softwood kraft pulps delignified at the Laboratory with xylanases in TCF bleaching sequences, before or after oxygen delignification, has shown advantages compared to the reference pulps (the Kappa number decreased, the brightness increased and there was minimal fiber degradation). Softwood kraft pulps bleached with Cartazyme NS-10 xylanase showed more brightness than softwood kraft pulps bleached with Pulpzyme HC xylanase. In addition enzymatic bleaching provided 20% savings of chemicals in oxidative peroxide extraction stage, which produced the following Kappa numbers: 5.1 (OXPAEOP), 5.2 (OXCAEOP), 5.5 (XPOAEOP), and 5.4 (XCOAEOP), while kraft pulp bleached without the enzyme stage had Kappa number 5.6. The brightness values for these sequences were: 69.0 %ISO (OXPAEOP), 68.8 %ISO (OXCAEOP), 67.8 %ISO (XPOAEOP), 68.4 %ISO (XCOAEOP) and 64.1 %ISO (OAEOP). Viscosity measurements gave: 16.4 cp (OXPAEOP), 16.9 cp (OXCAEOP), 17.0 (XPOAEOP), 18.2 cp (XCOAEOP), and 17.4 cp (sequence without the enzyme stage). Softwood kraft pulps bleached at Laboratory with xylanases had brightness increased when compared to kraft pulps bleached in Klabin-mill with CEH bleaching sequence (63.6 %ISO).